Social inequalities in indicators of use of healthcare services by adolescents in Campinas, São Paulo, Brazil - Vivian Castro Lemos; Marilisa Berti de Azevedo Barros; Margareth Guimarães Lima (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: This study aimed to analyze the prevalence of indicators of use of healthcare services according to sex, income and race/skin color, in adolescents (aged 10-19 years old) based on data from the Health Survey of the Municipality of Campinas (ISACamp), carried out in 2014/2015 in Campinas, São Paulo, Brazil. The chi-square test was used to evaluate the differences between the outcome variables (indicators of use of healthcare service) and sex, income and race/skin color. Adjusted prevalence ratios (PR) were estimated using Poisson multiple regression models. The demand for medical care was high in the last year of the interview (79.2%), mostly attended by the Brazilian Unified National Health System (65.2%), with routine consultations being more prevalent for females (PR = 1.17; 95%CI: 1.01-1.34) and injury for the male population (PR = 0.47; 95%CI: 0.26-0.84). Economic and racial differences were found in the evaluation of the last medical consultation, with a higher prevalence of worse care among those with lower income (PR = 1.46; 95%CI: 1.14-1.87) and black people (PR = 1.27; 95%CI: 1.01-1.61). Inequalities remained for delay or failure to carry out exams (PR = 1.64; 95%CI: 1.02-2.64) and worse quality of dental care (PR = 2.10; 95%CI: 1.38-3.21) in those with lower income. Also, black people had fewer appointments with dentists (PR = 0.90; 95%CI: 0.82-0.99).